686 Nuclear Transit Scintigraphy (Nts) - An Evolving Role from Diagnostic to Monitoring Tool in Children With Chronic Constipation. (October 2012) - Yik, YI; Cook, DJ; Veysey, DM; Tudball, CF; King, BS; Morris, KA; Cain, TM; Southwell, BR; Hutson, JM
Abstract : Purpose: Nuclear transit scintigraphy (NTS) is a relatively new investigation for children with intractable chronic constipation. Three patterns of colonic transit were identified: normal, slow and rapid colonic transit. We aimed to determine the use of NTS over the last 12 years at a tertiary institute. We hypothesised that NTS has evolved from a diagnostic to a monitoring tool. Methods: NTS were reviewed retrospectively (1999–2011) and characterized based on 3 different colonic transit patterns with further division into a new/repeat study (Ethics30059A). Statistical analysis was performed with Chi-square test to examine the effect of change; p<0.05 considered significant. Transcutaneous electrical stimulation (TES) was introduced to treat slow-transit constipation (STC) since 2006. Hence, we examined the changing role of NTS before and after TES use in STC children. Results: From 1999–2011, there were 955 NTS performed (667 new and 288 repeat studies): normal colonic transit - 133 new and 27 repeat; rapid colonic transit - 190 new and 24 repeat; slow colonic transit - 344 new and 237 repeat studies; with more repeat studies for STC children (p<0.0001, Chi-square). There was an increase of repeat studies from 1999–2005 (15%) to 2006–2011 (30%, p<0.0001). Since 2006, 95/237 (40%) NTS performed were repeat studies to monitor the effects of TES in STC children. Conclusion: NTS has is a useful diagnostic tool and helps to improve management of chronic constipation by guiding therapy, targeting the underlying dysmotility. It also provides objective assessment in monitoring response to therapy/intervention.